Pelayanan Pastoral sebagai Wujud Kasih Kristiani di Tengah Tantangan Zaman Modern: Menjawab Kebutuhan Spiritual dan Sosial Umat - Yohanes Chandra Kurnia Saputra (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
The modern challenges of secularization, hedonism, and moral relativism have threatened the spirituality of Christians, affecting the quality of pastoral ministry within society. Therefore, strategic and relevant efforts are necessary to address these challenges without losing the essence of Gospel values. This study aims to explore the role of pastoral ministry as an expression of Christian love in responding to these challenges and its relevance in the modern era. This focus is expected to provide practical solutions that promote the revitalization of faith within a changing societal context.The method used in this study is a literature review, examining various theological references and pastoral practices. The findings suggest that pastoral ministry based on Christian love can respond to contemporary challenges through community-based approaches and concrete social actions. Furthermore, this ministry must be contextual, leverage digital technology, and engage young people to maintain its relevance in an ever-evolving era. This underscores the need for synergy between profound faith traditions and innovative pastoral methods to reach a broader audience effectively. In conclusion, pastoral ministry plays a central role in the social and spiritual transformation of the faithful and requires renewal in its approach to remain relevant amid changing times. Therefore, dynamic and adaptive pastoral ministry is the key to creating a tangible impact on the lives of Christians.